A 4EX Music Composition Model: Design and Evaluation for Informal Learners - Yingchuan, He; Wangphanich, Chanick; Rodsakan, Tepika (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
China’s informal popular music training is uneven, and beginners lack systematic composition pathways. This article aimed to study (1) design and develop a music composition learning model for informal learners (2) examine the quality and efficiency of the music composition learning model, Using purposive sampling, 13 beginners aged 18–25 participated in a pilot implementation, and data were analyzed through expert review and descriptive statistics. The findings addressing the research objectives show that 10 experts confirmed the model’s high quality with suggestions for refinement, and the trial exceeded the 80/80 efficiency criterion (85.96/82.22). The model provides a structured and low-threshold pathway that supports informal learners in rapidly acquiring basic composition skills and expressing personal emotions through music creation.